Aetosauria: a clade of armoured pseudosuchians from the Upper Triassic continental beds - Desojo, Julia Brenda; Heckert, Andrew B.; Martz, Jeffrey W.; Parker, William G.; Schoch, Rainer; Small, Bryan J.; Sulej, Tomasz
Aetosauria is a clade of obligately quadrupedal, heavily armoured pseudosuchians known from Upper Triassic (late Carnian?Rhaetian) strata on every modern continent except Australia and Antarctica. As many as 22 genera and 26 species ranging from 1 to 6 m in length, and with a body mass ranging from less than 10 to more than 500 kg, are known. Aetosauroides scagliai was recently recovered as the most basal aetosaur, placed outside of Stagonolepididae (the last common ancestor of Desmatosuchus and Aetosaurus). Interrelationships among the basal aetosaurs are not well understood but two clades with relatively apomorphic armour ? the spinose Desmatosuchinae and the generally wide-bodied Typothoracisinae ? are consistently recognized. Paramedian and lateral osteoderms are often distinctive at the generic level but variation within the carapace is not well understood in many taxa, warranting caution in assigning isolated osteoderms to specific taxa. The aetosaur skull and dentition varies across taxa, and there is increasing evidence that at least some aetosaurs relied on invertebrates and/or small vertebrates as a food source. Histological evidence indicates that, after an initial period of rapid growth, lines of arrested growth (LAGs) are common and later growth was relatively slow. The common and widespread Late Triassic ichnogenus Brachychirotherium probably represents the track of an aetosaur. Fil: Desojo, Julia Brenda. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Heckert, Andrew B. Appalachian State University; Estados Unidos Fil: Martz, Jeffrey W. Denver Museum of Nature and Science; Estados Unidos Fil: Parker, William G. University of Texas; Estados Unidos Fil: Schoch, Rainer. Staatliches Museum für Naturkunde; Alemania Fil: Small, Bryan J. Museum of Texas Tech University; Estados Unidos Fil: Sulej, Tomasz. Instytut Paleobiologii; Polonia